In Silico Screening Inhibitors Histamine H2 Chemical Compounds in Licorice Plants (Glycyrrhiza glabra L.) Using Autodock Vina - Najib, Ahmad; Malik, Abd.; Sumartono, Sumartono (Jurnal Fitofarmaka Indonesia, 2023)
The inquiry about on in silico screening of chemical compounds of Histamine H2 of Liquorice (Glycyrrhiza glabra L.), aimed to get the potential bioactive compounds found in plants The Liquorice (Glycyrrhiza glabra L.) as a potential inhibitor Histamine H2 with a screening in silico by Autodock Vina Docking process is carried out on enzyme Histamine H2 as receptors and 105 chemical compounds in plants Liquorice (Glycyrrhiza glabra L.) as ligands using Autodock Vina program. ∆Gbind value and lowest RMSD of each compound that has been in the docking taken the value of the free energy change (∆G) as a result of docking. Docking results showed that of the 105 chemical compounds of plant Liquorice (Glycyrrhiza glabra L.)  are all potential as inhibitors Histamine H2  with free energy change (∆G) most low at Glabrene amounted to -9.6 kcal/mol, and the highest Isotachioside amounted to -4.5 kcal/mol.